MENINGKATKAN PRESTASI BELAJAR BAHASA INGGRIS MELALUI PEMBELAJARAN KOOPERATIF MODEL NUMBERED HEAD TOGETHER PADA SISWA KELAS IXC SMPN 3 MUARA BUNGO - Harneli Harneli (Journal Of Language Education and Development (JLed), 2021)
This research is motivated by the following problems: (a) Does the cooperative learning of the Numbered Head Together model affect English learning outcomes (b) How high is the level of mastery of English subject matter with the application of the Numbered Head Together cooperative learning method. The objectives of this study were: (a) To reveal the effect of cooperative learning of the Numbered Head Together model on English learning outcomes. (b) Want to know how much understanding and mastery of English subjects after the implementation of cooperative learning model Numbered Head Together.This research uses action research as many as three rounds. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The targets of this study were students of Class IXC at SMPN 3 Muara Bungo. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. The results showed that student learning achievement had increased from cycle I to cycle III, namely, cycle I (60.71%), cycle II (75.00%), cycle III (89.29%). The conclusion of this research is that the cooperative method of the Numbered Head Together model can have a positive effect on the learning motivation of the Class IXC students of SMPN 3 Muara Bungo and this learning model can be used as an alternative to English.